Proses Manajemen Program Corporate Social Responsibility In-LITE LED 2023 Oleh PT Prima Praxis Komunika - Mikha Puan Diandra; Retasari Dewi (Pusat Riset dan Inovasi Nasional, 2024)
Many companies utilize PR consultant services in their public relations programs, one of which is In-Lite LED as a client of PT Prima Praxis Komunika or Praxis. In-Lite LED together with Praxis collaborate in organizing external communication programs that require the role of the media, one of which is the in-Lite LED 2023 CSR program. This research aims to discuss in detail the program management process which includes the process of defining problems, planning, implementing action strategies and communication, and evaluation of the in-Lite LED 2023 CSR program by Praxis. This research uses descriptive qualitative methods based on interview data, observation and literature study. The results of this research show that the problem definition process includes an assessment of individual concerns regarding an external condition that can be improved, carrying out informal interviews and secondary analysis via the internet, conducting site surveys, understanding evaluations of previous CSR in-Lite LEDs, as well as conducting brainstorming with client. The planning process includes determining public targets, objectives, strategies and tactics, days, dates and duration of events, spokespersons and talking points, to preparing media documents and preparing other technical needs. The implementation process includes implementing action strategies in the form of CSR programs, implementing active coordination, and implementing communication strategies. Finally, the evaluation process includes media monitoring and internal evaluation of the organizer. Overall, the program management process has gone well, although Praxis can still maximize each process to obtain more in-depth evaluation results regarding the impact on the residents of Untungjawa Island after the program has taken place.